The The Influence of Job Insecurity on Workplace Deviance Behavior with Perceived Organizational Support as a Moderating Variable among Hotel Employees in Padang City. - Ogie deresky (Human Resource Management Studies, 2025)
Effective Human Resource Management is crucial for creating a positive work environment and preventing negative employee behavior. This study aims to analyze the influence of job insecurity on workplace deviance behavior, with perceived organizational support as a moderating variable. The research method used is a quantitative descriptive approach. Data was collected by distributing questionnaires to 100 hotel employees in Padang City and was analyzed using Structural Equation Modeling (SEM). The results show that job insecurity has a positive and significant effect on workplace deviance behavior. This indicates that feelings of job insecurity can trigger employees to exhibit deviance behavior in the workplace. Furthermore, perceived organizational support acts as a moderating variable that weakens the relationship between job insecurity and workplace deviance behavior. These findings prove that the higher an employee's perception of organizational support, the lower the negative impact of job insecurity on deviant behavior, especially among hotel employees.